Consensus of multi-agent systems with markov jump topologies and delays - Chen, C.; Yin, YanYan; Gu, D.; Liu, F. (ICIC International, 2018)
© 2018, ICIC International. All rights reserved. This paper investigates the problem of consensus for multi-agent systems with switching topologies and stochastic delays. The switching topologies and time-delays are governed by Markov chains. By using Lyapunov function approach, sufficient conditions are established such that consensus is achieved. A numerical example is provided to verify the effectiveness of the proposed approach.